Cefiderocol as Rescue Therapy for Acinetobacter baumannii and Other Carbapenem-resistant Gram-negative Infections in Intensive Care Unit Patients. (17th September 2020) - Falcone, Marco; Tiseo, Giusy; Nicastro, Manuela; Leonildi, Alessandro; Vecchione, Alessandra; Casella, Costanza; Forfori, Francesco; Malacarne, Paolo; Guarracino, Fabio; Barnini, Simona; Menichetti, Francesco
Abstract: Ten critically ill patients with either bacteremia or ventilator-associated pneumonia caused by carbapenem-resistant Acinetobacter baumannii, Stenotrophomonas maltophilia, or New Delhi metallo-β-lactamase–producing Klebsiella pneumoniae received cefiderocol. All strains had minimum inhibitory concentration ≤2 μg/mL. Thirty-day clinical success and survival rates were 70% and 90%, respectively. Two patients had a microbiological failure. Future prospective studies are warranted.